Ask Question
16 May, 13:18

Simplify with steps.

^^

1. (x-1) (5x+8) - 2x+5

2. (-2+5) (3x+9)

3. 2x+5-8x+12

4. (-x+3) (-5x-2)

0
Answers (1)
  1. 16 May, 14:48
    0
    1. (x-1) (5x+8) - 2x+5

    = (x) (5x) + (x) (8) + (-1) (5x) + (-1) (8) + -2x+5

    =5x2+8x+-5x+-8+-2x+5

    Combine Like Terms:

    =5x2+8x+-5x+-8+-2x+5

    = (5x2) + (8x+-5x+-2x) + (-8+5)

    =5x2 + x + - 3

    2. (-2+5) (3x+9)

    =9x+27

    3. 2x+5-8x+12

    =2x+5+-8x+12

    Combine Like Terms:

    =2x+5+-8x+12

    = (2x+-8x) + (5+12)

    =-6x+17

    4. (-x+3) (-5x-2)

    = (-x+3) (-5x+-2)

    = (-x) (-5x) + (-x) (-2) + (3) (-5x) + (3) (-2)

    =5x2+2x-15x-6

    =5x2 - 13x - 6
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “Simplify with steps. ^^ 1. (x-1) (5x+8) - 2x+5 2. (-2+5) (3x+9) 3. 2x+5-8x+12 4. (-x+3) (-5x-2) ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers